Strategies of the Choir Conductor in Developing the Vocal Quality of Eklesia Choir Members at Universitas Negeri Medan - Riau Wika (PT Ininnawa Paramacitra Edukasi, 2026)
This study is entitled “The Coach’s Strategies in Developing Vocal Quality of the Eklesia Choir Members at Medan State University”. The purpose of this study is to describe the strategies implemented by the coach in developing the vocal quality of the Eklesia Choir members at Medan State University. This research employed a qualitative approach using a descriptive method. Data were collected through observation, interviews, and documentation involving the coach and choir members. The results show that the trainer implements structured and gradual training strategies in the vocal coaching process of the choir members. These strategies include providing basic understanding of choir singing and voice classification, as well as training in fundamental vocal techniques such as diaphragmatic breathing, body posture, articulation, phrasing, resonance, and song interpretation. In addition, the trainer consistently applies vocalizing or vocal warm-ups with various exercises such as humming, lip trill, tongue trill, interval training, and articulation exercises using vowel sounds. During the training process, the trainer also applies demonstration, drill, and imitation methods to help members understand and practice vocal techniques directly. These training strategies not only improve the members singing techniques but also develop musicality, harmonic balance and cooperation among choir members. Therefore, the trainer’s strategies play an important role in systematically and sustainably developing the vocal quality of choir members.